Recovery of lead from smelting fly ash of waste lead-acid battery by leaching and electrowinning. (June 2016) - Chen, Chuh-Shun; Shih, Yu-Jen; Huang, Yao-Hui
Graphical abstract: Highlights: Fly ash of lead-acid battery smelting is constituted of anglesite and lanarkite. Pb in fly ash was leached in high concentrated HNO3 and NaOH. Ti-DSA or graphite anode and stainless steel cathode recovered Pb in leachant. Effect of anodes on PbO2 formation was assessed by cyclic voltammetry. Electrolysis of Pb was evaluated via current efficiency and energy consumption. Abstract: Fly ash that was enriched with lead (Pb), formed as an intermediate in waste lead-acid battery (WLAB) smelting, was recycled by the hydro-electrometallurgy. Characterization of fly ash thereof indicated that the Pb was in the forms of PbSO4 (anglesite) and Pb2 OSO4 (lanarkite). Nitric acid and sodium hydroxide were firstly used to study the leaching of the fly ash sample, which was affected by leachant dosage and solid-to-liquid ratio (S/L). At an S/L of 60 g L −1, the leachability of Pb was 43% and 67% in 2 M acidic and basic solutions, respectively, based on an average 70 wt% of Pb in the original fly ash. Anglesite was completely soluble in NaOH and lanarkite was mildly soluble in HNO3 . Pb was recovered from the pregnant leach solution within an electrolytic cell constructed with graphite or RuO2 /IrO2 -coated titanium (Ti-DSA) anodes and a stainless steel cathode. Properties of anodes deposited with lead dioxides were analyzed by cyclic voltammetry. The optimized parameters of electrowinning were 2 M NaOH leachant, a current density of 0.75 A dm −2 and an electrolytic process duration of 120 min, which yielded a Pb removal of higher than 99% and a specific energy consumption of 0.57 W h g −1 . This process constitutes an eco-friendly and economic alternative to the presently utilized secondary pyrometallurgy for treating lead-containing fly ash.